2006
DOI: 10.1073/pnas.0601407103
|View full text |Cite
|
Sign up to set email alerts
|

IgD, like IgM, is a primordial immunoglobulin class perpetuated in most jawed vertebrates

Abstract: IgD has remained a mysterious Ig class and a bane to immunology students since its discovery >40 years ago. Its spotty occurrence in mammals and birds and the discovery of an isotype with similarities to IgD in bony fish are perplexing. We have identified IgD heavy (H) chain (␦) from the amphibian Xenopus tropicalis during examination of the IgH locus. The Xenopus ␦ gene is in the same position, immediately 3 of the IgM gene, as in mammals, and it is expressed only in the spleen at low levels, primarily as a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
138
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 195 publications
(142 citation statements)
references
References 44 publications
(51 reference statements)
2
138
0
1
Order By: Relevance
“…The IgY in P. sinensis as well as in other vertebrates such as in amphibians (Amemiya et al, 1989;Warr et al, 1995) and avians (Zhao et al, 2000;Lundqvist et al, 2001), in which this Ig molecule is found, has also a conserved four constant domain structure. Phylogenetic analysis similarly indicated that the IgM and IgD in the Chinese soft-shelled turtle are well closely clustered with their counterparts reported in other reptiles, despite the variation in the number of constant domains in IgD in different classes of vertebrates and even in different species within same class of vertebrates (Wilson et al, 1997;Hordvik et al, 1999;Stenvik and Jorgensen, 2000;Hirono et al, 2003;Saha et al, 2004;Ohta and Flajnik, 2006;Deza and Espinel, 2008). The IgY, as indicated in the phylogenetic tree is closely related with those IgY found in avians; but its relationship with the GenBank deposited IgY sequence (GenBank accession no.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The IgY in P. sinensis as well as in other vertebrates such as in amphibians (Amemiya et al, 1989;Warr et al, 1995) and avians (Zhao et al, 2000;Lundqvist et al, 2001), in which this Ig molecule is found, has also a conserved four constant domain structure. Phylogenetic analysis similarly indicated that the IgM and IgD in the Chinese soft-shelled turtle are well closely clustered with their counterparts reported in other reptiles, despite the variation in the number of constant domains in IgD in different classes of vertebrates and even in different species within same class of vertebrates (Wilson et al, 1997;Hordvik et al, 1999;Stenvik and Jorgensen, 2000;Hirono et al, 2003;Saha et al, 2004;Ohta and Flajnik, 2006;Deza and Espinel, 2008). The IgY, as indicated in the phylogenetic tree is closely related with those IgY found in avians; but its relationship with the GenBank deposited IgY sequence (GenBank accession no.…”
Section: Discussionsupporting
confidence: 52%
“…IgX has been considered to be an analogue of mammalian IgA because a large number of IgXpositive B cells were preferentially expressed in the gut epithelium (Mussmann et al, 1996). The Xenopous ␦ gene (IgD, possess eight Cdomains) locates in the same gene cluster, following immediately 3 end of the IgM gene, as in mammals (Ohta and Flajnik, 2006). IgF heavy chain with only two constant domains, is similar to amphibian IgY in sequence, but its gene contains a hinge exon making it the earliest example in evolution of an Ig isotype with a separately encoded genetic hinge (Zhao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1A) are most homologous to the primordial IgW of sharks (14). Of the five human antibody classes, IgA, IgD, IgE, IgG, and IgM, IgW is most closely related to IgD, which, along with IgM, are the oldest Ig isotypes (14)(15)(16)(17). Except for low-resolution electron microscopic images (18), no structural data are available for any of the constant IgNAR domains.…”
mentioning
confidence: 99%
“…7). As IgM and IgD(W) are now commonly accepted to be the most primordial IgH classes in evolution 17,21,22 , it is reasonable to conclude that all other IgH classes evolved from them through various molecular mechanisms such as gene duplication, conversion or recombination. These processes gave rise to IgNAR and IgZ(T) after the divergence of cartilaginous fish and bony fish, respectively [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Differential diversification of the Ig classes or subclasses may have arisen from a long evolutionary period of environmental selection pressure, thus conferring survival advantages. IgM and IgD are thought to be the most primitive Ig classes 17,21 , as IgM has been identified in all species examined to date and IgD is found in most species except for birds and certain mammals 22 . Logically, other IgH (H: heavy-chain genes) classes should be evolutionarily derived from IgM and IgD, likely through various mechanisms such as gene duplication, gene conversion or recombination.…”
mentioning
confidence: 99%